Nigerian Children's Prose Fiction: A Critical Appraisal. - Fayose, Philomena Osazie Esigbemi (Obafemi Awolowo University, 2014)
The thesis attempts to draw attention to the much neglected field of children's literature on which very little critical work has so far been done.